FOSTERING LITERARY APPRECIATION THROUGH PROJECT-BASED LEARNING: A QUALITATIVE DESCRIPTIVE CASE STUDY AT SDN 5 KABILA - mile, yoga Aditama; Sulmin; Tomayahu, Heldina U; Ayuni, Sri; Toini, Nadya Putri; Sarabiti, Siti Musdhalifa; Nurul; Blongkod, Fadlika (LPPM STISIPOL Mujahiddin, 2025)
This study explores the implementation of Project-Based Learning (PjBL) in enhancing poetry appreciation among fifth-grade students at SDN 5 Kabila, Indonesia. Literary instruction in Indonesian primary schools often lacks creative depth, particularly in poetry, leading to limited student engagement and emotional expression. Adopting a qualitative descriptive case study approach, data were collected through semi-structured interviews, classroom observations, and visual documentation involving 22 students and one language teacher. Findings reveal that PjBL significantly improves student participation, confidence, and emotional articulation. Students actively engaged in writing, illustrating, and presenting their poems, fostering collaboration and creative autonomy. Teachers reported increased motivation and deeper literary understanding among learners. The study concludes that PjBL provides a transformative learning experience that bridges academic and affective growth in primary education. This research contributes to the growing discourse on constructivist approaches in language arts and offers practical insights for educators seeking to enrich poetry instruction through active, student-centered methodologies.